Using Historical Sites To Help Teach The United States Survey - Gallagher, Gary (Teaching History: A Journal of Methods, 1998)
Everyone who teaches the American history survey in the United States has at hand some historical site that can be integrated into the curriculum. It might be a house or a neighborhood, a road trace, a fort, an old canal or railroad bed, or the remains of an iron furnace. Whatever the nature of the site, it holds the potential to bring a piece of the past vividly to life for students too often conditioned to rely on electronic images to stimulate their imaginations. Historic sites permit students literally to touch our past, and in that moment to make a connection to earlier Americans and their lives that cannot be duplicated in any classroom.